The effect of NeuroTracker training on attention and decision-making speed in amateur youth boxers - Tanowsri, R.; Chainarong, A.; Putthithanasombat, K.; Hiruntrakul, A.; Philuek, P.; Kusump, S. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2026)
Background. Cognitive abilities such as attention and decision-making are critical components of performance in combat sports like boxing. NeuroTracker training has been proposed as a method to enhance these skills in athletes. Problem and aim. This study aimed to examine whether an eight-week NeuroTracker training program could improve attention and decision-making speed in youth amateur boxers.